HUKUM MENIKAHI SAUDARA PEREMPUAN MANTAN ISTRI: (Studi Komparatif Pemikiran Ulama Hanafiyah dan Syafi’iyah) - Darlius, Darlius (Al-Muqaronah: Jurnal Perbandingan Madzhab dan Hukum, 2024)
This research aims to find out how the opinions of Hanafiyah and Syafi'iyah on the law of marrying the wife's sister who has been divorced ba'in at the time of divorce. on the law of marrying the sister of a wife who has been divorced ba'in during her iddah her iddah lasts. This research uses a qualitative method with literature data as the primary source. primary source is the book of Fath al-Qodir and Al-Muhazzab Fi Fiqh Imam Shafi'i, then the data is analysed using contents analysis. using contents analysis. The results of the study explain that the reason Hanafiyah scholars prohibit men from marrying because there is still a legal marriage bond and the husband is still obliged to provide nafafaf (maintenance) and the husband is still obliged to provide maintenance during the iddah period, so the husband cannot marry his wife's sister as in the iddah period husband may not marry his wife's sister as Allah says in Surah An-Nisa verse 23. Whereas the opinion of the Shafi'iyah scholars is that the marriage has been divorce ba'in kubra, besides that the husband does not have the obligation to provide nafaqah during the iddah period to provide maintenance during the iddah period of divorce ba'in. So it is permissible for a husband who has divorced his wife with a ba'in divorce may marry the sister of his ex-wife sister of the former wife.